CONSIDERAÇÕES SOBRE AS ANOMALIAS DE FLUORETO NO SISTEMA AQUÍFERO BOTUCATU-PIRAMBÓIA, NA BACIA DO PARANÁ - Kimmelmann, A. A.; Rebouças, A. C.; Souza, J. C. S.; Rebouças, A. M.; Bastos F., F. W.; Heine, C. A. (Águas Subterrâneas, 1990)
indisponível